BENEFITS OF COMMUNICATIVE TEACHING SKILLS DURING THE LESSON (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article examines the benefits of Communicative Language Teaching (CLT) in the classroom, focusing on how the communicative approach enhances learners’ ability to use language effectively in real-life situations. Unlike traditional methods, CLT promotes meaningful communication, learner-centered instruction, and interaction-based activities. The article highlights the principles of CLT, its impact on the development of language skills, changes in teacher and student roles, and its effectiveness in preparing learners for authentic communication. The findings suggest that CLT creates a more engaging, practical, and motivating language learning environment.